PENGGUNAAN ANALISIS SWOT DALAM MENGEMBANGKAN KETERAMPILAN DAN POTENSI USAHA DODOL NANAS KECAMATAN SUNGAI GELAM MUARO JAMBI - Desi Anggraini Manik, Pratiwi Indah Sari (Universitas Batanghari Jambi, 2020)
This study aims to find out what analysis is used in the development of pineapple dodol business in the new tangkit village through the development of skills and business potential carried out in increasing production and sales. Based on the results of the study, the analysis used by researchers is almost the same as the dodol businessman, but the entrepreneurs have not developed the analysis into a force in the production, distribution and marketing of products on the market. The average strength of the entrepreneur depends on the skills possessed by the workforce and the potential of production and sales has started well because marketing has been done through the mass media and looking for new customers. Thus, it can be concluded that the SWOT analysis can be used to develop business potential skills if carried out thoroughly, namely increasing strengths and opportunities and avoiding the weaknesses and threats that will occur in the pineapple dodol business in the new tangkit village. Keywords : SWOT Analysis, Skills, Business Potential